Existence of Solutions for Random Impulsive Differential Equation with Nonlocal Conditions - Jose, Sayooj Aby; Usha, Venkatesh (International Journal of Computer Sciences and Engineering, 2025)
Impulsive differential equations deals with the study of the dynamic processes which undergo sudden changes. Since 1990’s many mathematicians have derived lots of results on differential equations undergoing impulsive effects. Problems including local initial condition and the problems including nonlocal conditions were considered in their work. But the deterministic impulsive differential equations fail to demonstrate many real life situations. And to handle such situations the concept of random impulsive differential equations were introduced. In this paper, we introduce random impulsive differential equations with nonlocal condition . The main aim of this paper to study the existence and uniqueness of solutions of random impulsive differential equations with nonlocal condition. For, we prove a result using fixed point theory technique.